An Analytical Study of Liquidity and Assets Management Ratio of Selected Automobile Company in India - Kishankumar M. Rathod; Abhishek D. Pandya (Celebes Scholar pg, 2021)
The primary objective of this research is to assess the liquidity and asset management positions of selected vehicle manufacturers and to give recommendations for improving their liquidity and asset management positions. The current research spans five years, from 2015-2016 to 2019-2020. Three organizations were chosen for this research, and five ratios were calculated: the current ratio, the liquidity ratio, the working capital turnover ratio, the total asset turnover ratio, and the fixed asset turnover ratio. ANOVA was employed to test the hypothesis. The research's principal results reveal that there is no statistically significant variation in the different asset management and liquidity ratios of chosen vehicle businesses during the study period. According to data interpretation, the comparison of all the selected three automobile industry's ratios indicates that Maruti Suzuki Ltd. is in a better position than the other selected automobile companies, as its average of the selected ratios is 12.85, which is higher than the other selected automobile companies. Thus, Maruti Suzuki Ltd. outperforms the other automotive manufacturers.